(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Formulation of the problem. The level of distribution in agrophytocenoses of pathogens of the genus Fusarium L. is global, therefore, the efforts of breeders are aimed at creating varieties of soft winter wheat resistant to ear fusarium and with high yields. Purpose. In populations of the third generation of soft winter wheat, to determine the selection value and homeostatics of ear productivity elements on a natural and artificial infectious background of fungi of the genus Fusarium L., and during mycological analysis of grain. Methods. General scientific - analysis; laboratory - determination of resistance (by acting on seeds of inoculum of fungi of the genus Fusarium L.), field - phenological, visual, biometric; statistical - processing of experimental data. Results. On an agar medium, for two years, a low level of infection of soft winter wheat seeds with pathogens of the genus Fusarium Link (from 0.7 to 3.1%) was noted. By the nature of the cleavages in the F2 populations, forms with a level of damage from 0 to 51.4% were isolated and high positive values of the degree of transgression were noted. In F3, the best hybrid combinations were isolated by the following features: the length of the main spike, the number of grains and the weight of grains from the main spike on three backgrounds of pathogens of the genus Fusarium L., in terms of breeding value and homeostasis, which made it possible to clarify the adaptive properties of the breeding material. On the natural background of pathogens, the highest breeding value in terms of head spike productivity was from 53 to 70% of hybrid populations, in terms of homeostasis - 23-53%. In terms of breeding value above the average value on the artificial background, from 7 to 63 % of populations were observed, in terms of homeostasis - 7-50 %. Mycological analysis of grain showed variations in breeding value from 47 to 63%, and in homeostasis – 43-50 %. Conclusions. Wheat grain was infected with the following Fusarium species: F. graminearum (3.1 %), F. culmorum (2.5 %), F. sporotrichiella (1.8 %), F. moniliforme (1.1 %) and F. oxysporum (0.7 %). The use of sources of resistance to fungi of the genus Fusarium L. in crosses: BILINMEVEN-49 / Natalka, MV 20-88 / Smuhlianka, Donskoi prostor / Slavna, Myronivska rannostyhla / CATALON ta (Mikon / ALMA) / Lehenda myronivska had a positive effect on the inheritance of resistance to Fusarium, and hybrid combinations created with their participation can be breeding donors of this trait. Based on the productivity of the main ear (based on three experiments), the following breeding-valuable hybrid populations were identified: MIP Kniazhna ↔ (MV 20-88 / Smuhlianka), MIP Kniazhna ↔ (BILINMEVEN-49 / Natalka), MIP Kniazhna ↔ (Donskoi prostor / Slavna), MIP Vyshyvanka ↔ (BILINMEVEN-49 / Natalka), Svitanok MYR ↔ (MYR rannostyhla. / CATALON), Avrora MYR ↔ (MYR rannostyhla / CATALON), etc.